Prevalence of pulmonary tuberculosis among adults in a rural sub-district of South India. - Vineet K Chadha; Prahlad Kumar; Sharada M Anjinappa; Sanjay Singh; Somashekar Narasimhaiah; Malathi V Joshi; Joydev Gupta; Lakshminarayana; Jitendra Ramchandra; Magesh Velu; Suganthi Papkianathan; Suseendra Babu; et al. (PLoS ONE, 2012)
BACKGROUND: We conducted a survey to estimate point prevalence of bacteriologically positive pulmonary TB (PTB) in a rural area in South India, implementing TB program DOTS strategy since 2002. METHODS: Survey was conducted among persons ≥ 15 years of age in fifteen clusters selected by simple random sampling; each consisting of 5-12 villages. Persons having symptoms suggestive of PTB or history of anti-TB treatment (ATT) were eligible for sputum examination by smear microscopy for Acid Fast Bacilli and culture for Mycobacterium tuberculosis; two sputum samples were collected from each eligible person. Persons with one or both sputum specimen positive on microscopy and/or culture were labeled suffering from PTB. Prevalence was estimated after imputing missing values to correct for bias introduced by incompleteness of data. In six clusters, registered persons were also screened by X-ray chest. Persons with any abnormal shadow on X-ray were eligible for sputum examination in addition to those with symptoms and ATT. Multiplication factor calculated as ratio of prevalence while using both screening tools to prevalence using symptoms screening alone was applied to entire study population to estimate prevalence corrected for non-screening by X-ray. RESULTS: Of 71,874 residents ≥ 15 years of age, 63,362 (88.2%) were screened for symptoms and ATT. Of them, 5120 (8.1%) - 4681 (7.4%) with symptoms and an additional 439 (0.7%) with ATT were eligible for sputum examination. Spot specimen were collected from 4850 (94.7%) and early morning sputum specimens from 4719 (92.2%). Using symptom screening alone, prevalence of smear, culture and bacteriologically positive PTB in persons ≥ 15 years of age was 83 (CI: 57-109), 152 (CI: 108-197) and 196 (CI :145-246) per 100,000 population respectively. Prevalence corrected for non-screening by X-ray was 108 (CI: 82-134), 198 (CI: 153-243) and 254 (CI: 204-301) respectively. CONCLUSION: Observed prevalence suggests further strengthening of TB control program.